2018
DOI: 10.1002/hipo.23006
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging reveals microstructural alterations in corpus callosum and associated transcallosal fiber tracts in adult macaques with neonatal hippocampal lesions

Abstract: To investigate the effects of neonatal hippocampal lesions on the microstructural integrity of the corpus callosum (CC) in adulthood, macaque monkeys (n = 5) with neonatal bilateral neurotoxic hippocampal lesion (Neo-Hibo) and sham-operated controls (Neo-C, n = 5) were scanned using magnetic resonance diffusion tensor imaging (DTI) technique at 8-10 years old. CC was segmented into seven regionsgrouped into anterior CC (rostrum, genu, rostral body and anterior midbody) and posterior CC (posterior midbody, isth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…strokes, accidental injury, neurosurgery, traumatic brain injury etc). Studies to date have focused on changes in resting-state correlated activity (i.e., 'functional connectivity') following lesions, which can correlate with behavioral recovery following stroke lesions (He et al, 2007) or with structural connectivity changes in white matter tracts (Meng et al, 2018;Shamy et al, 2010). Clinical studies are now also documenting brain changes over time following permanent injury resulting in neglect or aphasia (Saur et al, 2006;Berthier et al, 2011;Hartwigsen et al, 2019;Stockert et al, 2020;Umarova et al, 2016).…”
Section: Permanent Lesions and Fmrimentioning
confidence: 99%
“…strokes, accidental injury, neurosurgery, traumatic brain injury etc). Studies to date have focused on changes in resting-state correlated activity (i.e., 'functional connectivity') following lesions, which can correlate with behavioral recovery following stroke lesions (He et al, 2007) or with structural connectivity changes in white matter tracts (Meng et al, 2018;Shamy et al, 2010). Clinical studies are now also documenting brain changes over time following permanent injury resulting in neglect or aphasia (Saur et al, 2006;Berthier et al, 2011;Hartwigsen et al, 2019;Stockert et al, 2020;Umarova et al, 2016).…”
Section: Permanent Lesions and Fmrimentioning
confidence: 99%
“…In vivo macaque dMRI with 1–1.5 mm isotropic resolution has been widely reported and easily attainable with most 3T scanners and commercially available coils (Feng et al, 2017; Liu et al, 2016 ; Meng et al, 2018 ; Rane and Duong, 2011 ; Shen et al, 2019 ; Shimony et al, 2018; Weiss et al, 2022 ). 1.1 mm isotropic dMRI data has been acquired with a knee coil (Shimony et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies of the application of DTI in non-human primates for the investigation of TBI are ongoing. Seminal work has shown that DTI can provide outcome measures in non-human primates models of traumatic spinal cord injury (Ma et al, 2016 ) and the remodeling of brain circuits upon hippocampal damage (Meng et al, 2018 ). Although non-human primate models of TBI has been established (e.g., King et al, 2010 ), the logistics and the ethics of non-human primates have so far limited the availability for DTI investigations.…”
Section: Applications To Models Of Neurodegenerative Diseasesmentioning
confidence: 99%